The Effects Of High Dose and Low Dose Protocols In Thorax’s CT Scan Image Quality - Ni Larasati Kartika Sari; Deni Tiko Bahagia; Puji Hartoyo; Dewi Muliyati (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
ABSTRACTThe aim of this research was to evaluate the effects of two different dose protocols’ usage on image quality. This research was performed on three different CT Scanners using high dose and low dose protocols of thorax scan. Different exposure parameters were used, depending on each scanner’s setting. GE QA CT Scan phantom was used for image quality assessment.  Image quality measured were CT number accuracy, uniformity and linearity, noise uniformity, spatial resolution and Contrast To Noise Ratio (CNR). CT Scan’s dose index, CTDIvol (Volumetric Computed Tomography Dose Index), was also measured to evaluate how these two protocols work in reducing radiation dose. The result showed that the usage of low dose protocols reduce the CTDIvol value at 85-91% compared to the high dose protocols, meanwhile most of the image quality parameters obtained from both protocols were still considered good. The CT number accuracy, uniformity, linearity and noise uniformity for all CT Scans were all still inside BAPETEN’s (Indonesia National Regulator Agency) threshold. There were 20-23% difference on the spatial resolution value measured from both protocols. The most significant difference came from CNR. The CNR obtained from high dose protocols were 65-93% higher than the one from low dose protocols.   Keywords: contrast to noise ratio, CTDIvol, CT number, spatial resolutionABSTRAKPenelitian ini mengevaluasi pengaruh penggunanaan protokol dosis tinggi dan protokol dosis rendah terhadap kualitias citra dan dosis khususnya pada pemeriksaan CT Scan thorax. Penelitian ini dilakukan pada 3 sampel CT Scan yang berbeda. Faktor eksposi yang digunakan berbeda untuk tiap scanner, bergantung pada setting yang terdapat pada scanner. Fantom yagdigunakan untuk menilai kualitas citra adalah fantom GE QA CT Scan. Adapun kualitas citra yang diukur adalah keseragaman, akurasi, dan linearitas CT number, keseragaman noise, resolusi spasial, serta Contrast to Noise Ratio (CNR). Sementara dosis radiasi yang diamati adalah CTDIvol (Volumetrik Computed Tomography Dose Index) yang tampil pada konsol. Hasil penelitian ini menunjukkan bahwa penggunaan protokol dosis rendah mampu mengurangi nilai CTDIvol sebesar 85-91% dibanding dengan protokol dosis tinggi, sementara sebagian besar parameter kualitas citra yang diukur masih dinilai baik. Nilai akurasi, keseragaman, dan linearitas CT number  serta keseragaman noise pada protokol dosis tinggi dan dosis rendah, keseluruhannya masih dalam batas ambang BAPETEN. Terdapat perbedaan sebesar 20-23% pada nilai resolusi spasial yang terukur dari  kedua protokol. Nilai CNR pada protokol dosis tinggi lebih baik dari pada protokol dosis rendah, dengan perbedaan yang cukup signifikan, yaitu 65-93%.Kata kunci: contrast to noise ratio, CTDIvol, CT number, resolusi spasial